Marco Polo. The complete first season [videorecording (DVD)] - Yune, Rick, 1971-; Chen, Joan, 1961-; Richelmy, Lorenzo; Wong, Benedict (Anchor Bay Entertainment, 2015)
In a world replete with greed, betrayal, sexual intrigue and rivalry, the series is based on the famed explorer's adventures in Kublai Khan's court in thirteenth century China.